Understanding vascular development: WIRE Developmental Biology (2012) - Udan, Ryan S. (2012)
The vasculature of an organism has the daunting task of connecting all the organ systems to nourish tissue and sustain life. This complex network of vessels and associated cells must maintain blood flow but constantly adapt to acute and chronic changes within tissues. While the vasculature has been studied for over a century, we are just beginning to understand the processes that regulate its formation and how genetic hierarchies are influenced by mechanical and metabolic cues to refine vessel structure and optimize efficiency. As we gain insights into the developmental mechanisms, it is clear that the processes that regulate blood vessel development can also enable the adult to adapt to changes in tissues that can be elicited by exercise, aging, injury, or pathology. Thus, research in vessel development has provided tremendous insights into therapies for vascular diseases and disorders, cancer interventions, wound repair and tissue engineering, and in turn, these models have clearly impacted our understanding of development. Here we provide an overview of the development of the vascular system, highlighting several areas of active investigation and key questions that remain to be answered.